Spillover Effects of Scandals on Exits from the Catholic and Protestant Churches in Germany. Issue 3 (6th May 2021) - Frick, Bernd; Moser, Katharina; Simmons, Rob
Abstract: For decades, the annual numbers of exits of members from the Catholic Church and Protestant Church have been increasing. Closer inspection of diocese‐level data shows that the time‐series pattern of exits is nonlinear with a series of intermediate peaks. This paper uses an event study approach to model the impacts of various scandals on church exit rates. We find that sexual abuse and financial scandals located in the Catholic Church contribute to increased exit rates not just in that Church but also, by way of spillover effects, to higher exit rates of Protestant Church members.